Squaring the Circle Between Freedom of Expression and Platform Law - Karanicolas, Michael (Pittsburgh Journal of Technology Law & Policy, 2020)
Among the greatest emerging challenges to global efforts to promote and protect human rights is the role of private sector entities in their actualization, since international human rights rules were designed to apply primarily, and in many cases solely, to the actions of governments. This paradigm is particularly evident in the expressive space, where private sector platforms play an enormously influential role in determining the boundaries of acceptable speech online, with none of the traditional guardrails governing how and when speech should be restricted. Many governments now view platform-imposed rules as a neat way of sidestepping legal limits on their own exercise of power, pressuring private sector entities to crack down on content which they would be constitutionally precluded from targeting directly. For their part, the platforms have grown increasingly uncomfortable with the level of responsibility they now wield, and in recent years have sought to modernize and improve their moderation frameworks in line with the growing global pressure they face. At the heart of these discussions are debates around how traditional human rights concepts like freedom of expression might be adapted to the context of “platform law.” This Article presents a preliminary framework for applying foundational freedom of expression standards to the context of private sector platforms, and models how the three-part test, which lies at the core of understandings of freedom of expression as a human right, could be applied to platforms’ moderation functions.